Pengaruh Penggunaan Platform Merdeka Mengajar terhadap Kesiapan Guru dalam Implementasi Kurikulum Merdeka - Kartikasari, Dewi; Puspitasari, Nimas; Sarwono, Ridha (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
In 2023, the independent curriculum will begin to be implemented in schools. Even though in its implementation there are still many obstacles. The Ministry of Education and Culture issued a policy regarding the use of the independent teaching platform (PMM) as a means that can support and facilitate teachers in preparing to implement the independent curriculum. This research aims to determine the effect of using the independent teaching platform (PMM) on teacher readiness in implementing the independent curriculum in the Gatot Subroto cluster environment, East Ungaran District, Semarang Regency.The research method used is quantitative research with a survey research design. The population of this research is all class teachers and subject teachers in schools that are members of the Gatot Subroto Korwilcam cluster for Education in East Ungaran District, totaling 68 people. The sample was selected by purposive sampling with a sample size of 24 teachers. This research was conducted in May 2023 in the Gatot Subroto cluster, East Ungaran District, Semarang Regency. Data collection techniques using questionnaires and documentation. The results of the simultaneous correlation calculation were 2.389, with a significance level of 0.05 and 0.136, indicating that there was no significant influence in the use of the independent teaching platform (PMM) on teacher readiness in implementing the independent curriculum.Keywords: Independent Teaching Platform (PMM), Implementation of the Independent Curriculum